The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.18488/journal.75/2014.1.1/75.1.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction and Calibration of a Solar Radiation Measuring Meter

Abstract: A digital solar radiation measuring instrument has been designed, constructed and calibrated. It incorporates a small rectangular silicon photocell as the sensor. On exposure to solar radiation, electromotive force which is proportional to radiation intensity is developed within the circuit. The device correlates voltage developed with available solar intensity. A standard solarimeter was therefore used to calibrate the device to translate the unit of its reading from Volt to Watt per square meter. Intensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In 2014, a remarkable investigation was undertaken by Daniel Asiegbu and Echeweozo Odinakachi, whose study cantered on the creation, fabrication, and alignment of a solar irradiance gauge. The study demonstrated the accuracy of their design in measuring solar radiation levels, making it a valuable tool for solar energy systems and related applications [21]. Frank Vignola also examined the evaluation of the diffuse response of pyranometers based on solar cells.…”
Section: Introductionmentioning
confidence: 97%
“…In 2014, a remarkable investigation was undertaken by Daniel Asiegbu and Echeweozo Odinakachi, whose study cantered on the creation, fabrication, and alignment of a solar irradiance gauge. The study demonstrated the accuracy of their design in measuring solar radiation levels, making it a valuable tool for solar energy systems and related applications [21]. Frank Vignola also examined the evaluation of the diffuse response of pyranometers based on solar cells.…”
Section: Introductionmentioning
confidence: 97%